2019
DOI: 10.20956/icon.v3i2.4972
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Nurses’ Compliance in Implementing Standard Precautions in Government Hospital in Yogyakarta

Abstract: Background:Nosocomial infection is infections that occur in patients when they are hospitalized. Data in several countries found that hundreds of millions patients worldwide are exposed to nosocomial infection each year. Standard precautions are applied to prevent infections in the hospital. The results of observations and interviews on nurses at Wates Regional Public Hospital found non-compliance of nurses in implementing standard precautions.Objective:The aim of this study is to determine factors affecting n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
2
0
3
Order By: Relevance
“…However, based on the results of the study, somebody found that from the number of respondents (84.4%) who had good knowledge about the use of PPE, only some respondents (52.6%) had a good perception of risk, meaning that respondents knew that the use of PPE needed to be applied in services. To patients but respondents only consider the use of PPE to prevent the possibility of which states that there is no significant relationship between barriers to using PPE (10).…”
Section: Resultsmentioning
confidence: 99%
“…However, based on the results of the study, somebody found that from the number of respondents (84.4%) who had good knowledge about the use of PPE, only some respondents (52.6%) had a good perception of risk, meaning that respondents knew that the use of PPE needed to be applied in services. To patients but respondents only consider the use of PPE to prevent the possibility of which states that there is no significant relationship between barriers to using PPE (10).…”
Section: Resultsmentioning
confidence: 99%
“…Hasil penelitian yang dilakukan di RS Aceh menunjukkan bahwa sebagian besar perawat pelaksana memiliki perilaku yang baik dalam penerapan manajemen Kesehatan dan Keselamatan Kerja (K3), dilihat dari faktor internal (52.5%) maupun factor eksternal (58.8%) (Nazirah & Yuswardi, 2017). Hasil penelitian yang menunjukkanfaktor yang mempengaruhi kepatuhan perawat di RS Pemerintah Yogyakarta terhadap kewaspadaan standard meliputi motivasi dan pengalaman kerja, dimana faktor yang paling dominan mempengaruhi kewaspadaan standard sebagai penerapan K3 yaitu motivasi (Sagita, 2019).…”
Section: Hasilunclassified
“…Hasil penelitian yang menunjukkan faktor yang mempengaruhi kepatuhan perawat di RS Pemerintah Yogyakarta terhadap kewaspadaan standard meliputi motivasi dan pengalaman kerja, dimana faktor yang paling dominan mempengaruhi kewaspadaan standard sebagai penerapan K3 yaitu motivasi (Sagita, 2019). Motivasi dan pengalaman kerja mempengaruhi kepatuhan perawat dalam melaksanakan kepatuhan penerapan konsep Keselamatan dan Kesehatan Kerja.…”
Section: Sehingga Kepercayaan Ini Yang Mendasari Perawat Untuk Menerapkan Kesehatan Danunclassified
“…Hal ini ditunjukkan dengan dari faktor internal (52.5%) maupun faktor eksternal (58.8%) (Nazirah & Yuswardi, 2017). Hasil penelitian yang menunjukkan faktor yang mempengaruhi kepatuhan perawat di RS Pemerintah Yogyakarta mengenai standar kewaspadaandalam hal ini adalah motivasi serta pengalaman kerja, dimana faktor yang paling mempengaruhi standar kewaspadaan sebagai penerapan K3 yaitu motivasi (Sagita, 2019).…”
Section: Hasilunclassified